The methodology of Machiavelli’s work «The Prince»: Is Machiavelli an early positivist? - Evaghorou, Evaghoras L. (The Greek Review of Social Research, 2019)
The identification and evaluation of the way Machiavelli elaborated his work «The Prince» is a process that refers to the examination and analysis of the characteristics of the author’s methodology. This process leads to the test of the hypothesis whether «The Prince» has positivist characteristics with regards to the way it had been structured. Presenting the main principles of positivism which had been developed the 1970 decade in the science of International Relations, it is examined the correlation between Machiavelli’s methodology in «The Prince» and the positivist characteristics. The research concludes that Machiavelli’s methodology in «The Prince» has several elements of the positivist methodology although in some of them deviates.